Yearbook of China city competitiveness 2012 - Gui, Qiangfang 1957-; Sit Fungshuen, Victor; Chen, Riqing 1979- (bEnrich Professional Publishing, 2013)
Up-to-date data on 297 Chinese cities with comprehensive coverage of more than 300 indicator. Complied by the China Institute of City Competitiveness and the Advanced Institute for Contemporary China Studies of Hong Kong Baptist University, the Yearbook of China City Competitiveness 2012 is the first comprehensive title analyzing China's city competitiveness. This book provides a comprehensive analysis of 297 cities